Quantitative analysis of amphetamine in femoral blood from drug-poisoning deaths compared with venous blood from impaired drivers. (October 2011) - Jones, Alan Wayne; Holmgren, Anita; Ahlner, Johan
Background: Amphetamine is a major drug of abuse worldwide. Here we compare the concentrations of this stimulant amine in femoral blood in drug fatalities with venous blood from impaired drivers.Method: Amphetamine was determined in blood by isotope-dilution GC–MS after liquid–liquid extraction.Results: Amphetamine was the only drug identified in 36 fatalities at mean (median) and highest concentrations of 2.0 mg/l (1.5 mg/l) and 14.0 mg/l. In multiple-drug deaths (n = 383), the concentrations were 0.94 mg/l (0.4 mg/l) and 13.3 mg/l. In impaired drivers with amphetamine as the only drug (n = 6138), the concentrations were 1.0 mg/l (0.8 mg/l) and 11.9 mg/l, compared with 0.78 mg/l (0.6 mg/l) and 22.3 mg/l in multidrug users (n = 8250).Conclusion: Fatal amphetamine poisonings cannot be identified on the basis of the concentration in blood alone, owing to the development of tolerance and the toxicity of co-ingested substances.